2017
DOI: 10.1186/s40643-017-0153-9
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization of a sulfonated textile dye Reactive Red 31 from simulated wastewater using pellets of Aspergillus bombycis

Abstract: BackgroundReactive Red 31, applied extensively in the commercial textile industry, is a hazardous and persistent azo dye compound often present in dye manufacturing and textile industrial effluents. Aspergillus bombycis strain was isolated from dye contaminated zones of Gujarat Industrial Development Corporation, Vatva, Ahmedabad, India. The decolorization potential was monitored by the decrease in maximum absorption of the dye using UV–visible spectroscopy. Optimization of physicochemical conditions was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Similarly, Chen and Ting [ 48 ] reported that colour removal of Methyl Violet, Crystal Violet and Malachite Green appeared to be better at lower initial dye concentrations by Coriolopsis sp. Khan and Fulekar [ 49 ] simulated wastewater using Aspergillus bombycis for dye decolourisation of a sulfonated textile dye, Reactive Red 31, and demonstrated that after incubation for 12 h, dye concentration was decreased from 99.76 to 91.06% as the concentration increased from 5 to 25 mg L −1 . As they described, the efficiency of the dye decolourisation depended on the initial concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Chen and Ting [ 48 ] reported that colour removal of Methyl Violet, Crystal Violet and Malachite Green appeared to be better at lower initial dye concentrations by Coriolopsis sp. Khan and Fulekar [ 49 ] simulated wastewater using Aspergillus bombycis for dye decolourisation of a sulfonated textile dye, Reactive Red 31, and demonstrated that after incubation for 12 h, dye concentration was decreased from 99.76 to 91.06% as the concentration increased from 5 to 25 mg L −1 . As they described, the efficiency of the dye decolourisation depended on the initial concentration.…”
Section: Resultsmentioning
confidence: 99%
“… [ 132 ] 2 Industrial textile effluent Chaetomium globosum IMA1 KJ472923 [ 133 ] 3 Reactive green dye [RGD] Fungal strain VITAF-1 [ 134 ] 4 Crystal Violet and Cotton Blue Coriolopsis sp. [ 135 ] 5 Congo Red Phoma tropica MRCH and Dichotomomyces cejpii MRCH 1–2 [ 136 ] 6 Crystal violet Trichoderma asperellum [ 137 ] 7 Reactive Red 31 Aspergillus bombycis [ 138 ] 8 Reactive Violet 5 and Reactive Black 5 [diazoic] Trametes trogii [ 139 ] 9 Scarlet RR Peyronellaea prosopidis [ 140 ] 10 Different azo dyes Aspergillus flavus [ 120 ] 11 Poly R Pseudoglarobasidium acaciicola [ 141 ] 12 Direct Red 128 and Direct Blue ...…”
Section: Treatment Methodsmentioning
confidence: 99%
“…Barapatre et al [82] reported Aspergillus flavus for biodegradation of Malachite Green in which intermediate N-demethylated and N-oxidized metabolites were identified [Figure 1]. Fungal strain Aspergillus bombycis was reported for having the ability to degrade Reactive Red 31 [83]. Asses et al [84] reported Aspergillus niger having the ability to decolorize Congo red (200 mg/L) within 6 days of incubation [Figure 2].…”
Section: Fungimentioning
confidence: 99%